PENGARUH LATIHAN SKIPPING TERHADAP PENINGKATAN CARDIOVASCULAR ENDURANCE PADA ANAK USIA SEKOLAH 10-12 TAHUN DI SDN PLUMBON 02 KECAMATAN SURUH KABUPATEN SEMARANG - Silvia Rahmawati; Budiyati Budiyati; Nina Indriyawati (Poltekkes Kemenkes Semarang, 2016)
[THE INFLUENCE OF SKIPPING EXCERSICE TO INCREASED CARDIOVASCULAR ENDURANCE ON SCHOOL AGE CHILDREN 10-12 YEARS IN ELEMENTARY SCHOOL PLUMBON 02 SURUH SUB –DISTRICT SEMARANG REGENCY] The current phenomena, many children and parents who ignore the importance of sports to physical fitness and endurance of the heart. Cardiovascular endurace which will both improve the working abilities of the child with greater intensity and longer without fatigue. The purpose of this research was to describe the influence of skipping exercise to increased cardiovascular endurance on school age children 10-12 years.The type of research used was pre-experimental research designs with one group pre-post test. The sample consists of 21 children of school age 10 – 12 years old. The entire sample was given skipping workouts as much as 8 times within 10 minutes of each meeting and implemented in the morning between 07.00 – 09.00 pm. The implementation of the pre-and post test-test using Rockport Walking Fitness Test to assess cardiovaskular endurance. The results of the analysis of simple paired t-test showed that there is a difference between data pre-and post test-test with p value = 0000. There was an influence of skipping exercise to increased cardiovascular endurance on school age children 10-12 years.